The Role of Teaching Bridges Program in Developing Educational Process from The Point of View of Public School Principals in Ajloun Governorate - Aluroad, Hamzeh Abd Almajeed Mahmood (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the role of teaching bridges program in developing educational process from the point of view of public school principals in Ajloun governorate, the researcher used the Descriptive approaches, study Sample consisted from (100) Female and male principals, chosen in an intentional stratified manner, to collect data Questioner used, which consisted (25) paragraph, the result of SPSS analysis shown that the degree of orate the role of teaching bridges program in developing educational process from the point of view of public school principals in Ajloun governorate was High with average (3.92 out of 5) , The finding also showed there is no statistically significant differences at (α≤0.05) refers to principal sex (male and female) in addition there weren’t statistically significant differences between the principals years of experience. According to the result a set of recommendation and suggestion to activate the Teaching Bridge to improve the in Ajloun Governorate schools and all of Kingdom and Arab countries.
Keywords: Teaching Bridges Program; Improving Educational Process; School Principals Perspective; Ajloun